Mithuna sculptures on mancha - Temples of India Project Team (Jio Institute, 2024)
Couples invoking shringara rasa (associated with romance, love, and attractiveness between lovers) are framed in panels with pillars and shikhara with gavashka (horseshoe) motifs. They sport elaborate coiffure and wear jewellery, indicating they are royalty. The panel is richly detailed, featuring nine figures. The central male figure is seated on a raised throne in a lalitasana pose with the central female figure seated in a padmasana pose. The man is facing the woman and caressing her chin with his left hand and holding a flower in his right hand. The female has her right hand placed over the man’s right shoulder and her left hand rests upon the head of a female attendant seated on the ground. The man is resting his right foot on a lotus next to a musician playing the flute (bottom left). Three more attendants appear on the left, the largest holding a fan. On the right, a female attendant (top right) is holding a fly whisk and another, the larger figure, is standing in a tribhanga pose and playing a musical instrument.